2019
DOI: 10.3126/nje.v9i2.24684
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge regarding breast self-examination among the women in Nepal: A meta-analysis

Abstract: Background: Screening interventions for the early diagnosis of breast cancer are associated with better clinical outcomes. Developing nations such as Nepal reportedly have lesser frequency of female university graduates (UGs) and therefore public awareness and education remains central in the early diagnosis. The current meta-analysis was aimed to assess the knowledge about breast self-examination (BSE) among women of Nepal. Materials and Methods: We have conducted the literature search using electronic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 16 publications
2
4
0
Order By: Relevance
“…In this study, the proportion of students with good knowledge on BSE was 27.6%. This finding is comparable with studies done in Debre Berhan, Ethiopia (30%) [ 16 ], Eretria (30.1%) [ 18 ], and Nepal (27%) [ 19 ]. However, the proportion of knowledge in this study is much lower than what was reported in India (93.3%) [ 17 ], Korea (87.0%) [ 20 ], Saudi (79.0%) [ 21 ], Uganda (76.5%) [ 22 ], Nigeria (55.4%) [ 23 ], and Egypt (63.4%) [ 24 ].…”
Section: Discussionsupporting
confidence: 89%
“…In this study, the proportion of students with good knowledge on BSE was 27.6%. This finding is comparable with studies done in Debre Berhan, Ethiopia (30%) [ 16 ], Eretria (30.1%) [ 18 ], and Nepal (27%) [ 19 ]. However, the proportion of knowledge in this study is much lower than what was reported in India (93.3%) [ 17 ], Korea (87.0%) [ 20 ], Saudi (79.0%) [ 21 ], Uganda (76.5%) [ 22 ], Nigeria (55.4%) [ 23 ], and Egypt (63.4%) [ 24 ].…”
Section: Discussionsupporting
confidence: 89%
“…Similar findings was reported by Altunkurek& Hassan Mohamed in Somaliya ( 2022) , which reported that only 35.4% of participants had information about breast cancer, 37.8% had heard about breast self examination and 25.2% knew about breast self examination. Similar findings was reported by Sathian ( 2019) on the meta analysis of Knowledge regarding breast self-examination among the women in Nepal, which revealed that the vast majority of females in the developing nations are unaware about performing regular breast self-examination (BSE) and thus have a lower rate of BSE. This could be attributed to the fact that women in the developing countries are afraid of finding that they have breast cancer, inappropriate knowledge in performing BSE and ignorance about the measures if a lump is identified.…”
Section: Discussionsupporting
confidence: 83%
“…A Turkish study concluded that nurses as health care professionals could play a key role in educating women about BSE. 9 Study shows that these personal fears such as the fear of physicians and doctors, fear of the results as well as the fear of hospitals are some of the main barriers for not practicing screening of breast cancer 14 .…”
Section: Education Status Discussionmentioning
confidence: 99%